Real‑Time Subsea Control System Compatibility Modeling for IWOCS and ROCS Integration in Multi‑Vendor Deepwater Operations - Malvern Iheanyichukwu Odum; Iduate Digitemie Jason; Dazok Donald Jambol (International Journal of Scientific Research in Civil Engineering, 2023)
In multi-vendor deepwater operations, the integration of Intervention Workover Control Systems (IWOCS) and Remote Operated Control Systems (ROCS) presents a significant challenge due to variations in hardware configurations, communication protocols, and control logic across equipment manufacturers. This paper proposes a real-time compatibility modeling framework designed to address these integration barriers by enabling proactive validation and operational synchronization between IWOCS and ROCS systems. The model is structured around a layered architecture encompassing hardware abstraction, protocol bridging, signal timing validation, and real-time logic mapping. The model standardizes control commands, feedback signals, and failure responses through functional equivalence mapping, ensuring operational consistency across disparate systems. A real-time validation engine continuously monitors system behavior to detect command mismatches, communication anomalies, and timing discrepancies during joint operations. Implementation guidance is provided for offshore integration with SCADA and DCS systems, HMI alignment for operator clarity, and early-phase testing during FAT and SIT. Drawing from recurring industry integration challenges, the paper underscores the value of pre-deployment calibration and cross-vendor coordination. Future research directions include integration with digital twins, development of automatic protocol conversion engines, and advancement toward standardized control system interfaces. The proposed framework enhances subsea system reliability, reduces non-productive time, and fosters greater interoperability in complex offshore environments.